Riometer Records of 30 MHz Cosmic Noise at Syowa Station, Antarctica in 1971 - オガタ, タカノブ; オセ, マサミ; OGATA, Takanobu; OSE, Masami (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper